Unleashing the ar-Rahnu as a micro-financing instrument for micro-entrepreneurs in Malaysia - Nik Azman, Nik Hadiyan; Md Zabri, Mohd Zaidi; Kassim, Salina; Abdul Kader Malem, Nurhafiza (Human Resource Management Academic Research Society, 2020)
The purpose of this paper is to compare the Islamic micro-financing and Ar-Rahnu. Using the content analysis approach, the paper examines the reports of micro-financing provided by Bank Negara Malaysia and comparing the rate with Ar-Rahnu. To validate the content analysis facts and to reveal the actual behavior and perception of micro-entrepreneurs towards ArRahnu, this study also conducted in-depth interview. The results show significant advantages of Ar-Rahnu as a better option as compared to the Islamic micro-financing as Ar-Rahnu has the lowest pricing charges, offer higher margin and lesser procedures required. In fact, ArRahnu also have skilled employees reflected to their customer satisfaction and updated with the current technology of innovation (fintech). This paper’s contribution to the literature is by including a comparison between the products within the Islamic financial system setting. Besides, in term of methodology, this study used multiple approaching techniques of qualitative method which are content analysis and in-depth interview.